Bismuth(iii) triflate-catalysed tandem cyclisations towards complex polycyclic ethers. Issue 8 (29th June 2016) - Ondet, Pierrick; Lempenauer, Luisa; Duñach, Elisabet; Lemière, Gilles
Abstract : A series of complex polycyclic ethers have been synthesised under very mild conditions using a low catalyst loading of bismuth(iii ) triflate. Abstract : Herein is described a double cyclisation of α-hydroxy enol ethers with a tethered olefinic double bond, readily obtained from simple ketone precursors. Interesting bridged polycyclic compounds with an additional oxaspirocycle are formed under mild conditions using a low loading of recyclable bismuth(iii ) triflate as the catalyst. Some experimental evidence accounts for concerted (or pseudo-concerted) polycyclisation.